Evolutionary Biology : Conceptual, Ethical, and Religious Issues / [electronic resource] - Thompson, R. Paul; Walsh, Denis (Cambridge : Cambridge University Press, 2014)
Evolution - both the fact that it occurred and the theory describing the mechanisms by which it occurred - is an intrinsic and central component in modern biology. Theodosius Dobzhansky captures this well in the much-quoted title of his 1973 paper 'Nothing in biology makes sense except in the light of evolution'. The correctness of this assertion is even more obvious today: philosophers of biology and biologists agree that the fact of evolution is undeniable and that the theory of evolution explains that fact. Such a theory has far-reaching implications. In this volume, eleven distinguished scholars address the conceptual, metaphysical and epistemological richness of the theory and its ethical and religious impact, exploring topics including DNA barcoding, three grand challenges of human evolution, functionalism, historicity, design, evolution and development, and religion and secular humanism. The volume will be of great interest to those studying philosophy of biology and evolutionary biology.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Evolution (Biology)